INOVASI PRODUK BOLU PISANG DENGAN SUBSTITUSI SARI KURMA - Chantika Aleida Putri; Priyanto (Eduturisma, 2023)
This research aims to determine the process of making banana cake with the substitution of sugar with date juice and to determine the level of people's preference for banana cake with the substitution of date juice. The method used is the experimental method. Researchers used this method to add date juice and reduce granulated sugar. The results of the research show that the process or method for making banana cakes with date juice substitution is the same as making banana cakes in general, the only difference is that there is a date juice substitution in each dough. The test results of respondents' preferences for banana cake with date juice substitution were based on four criteria, namely aroma, color, taste and texture. In terms of aroma and taste, products with 25% substitution are preferred, while in terms of color and texture, products with 70% substitution are preferred. Improving the quality and increasing nutritional value of banana cake, such as increasing vitamins, minerals and fiber, could have positive implications for consumers looking for healthy cakes.